2018
DOI: 10.3390/coatings8020058
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Barrier Properties of Potato Protein Isolate-Based Films

Abstract: Potato protein isolate (PPI) was studied as a source for bio-based polymer films. The objective of this study was the determination of the packaging-relevant properties, including the mechanical properties and barrier performance, of casted potato protein films. Furthermore, the films were analyzed for cross-linking properties depending on the plasticizer concentration, and compared with whey protein isolate (WPI)-based films. Swelling tests and water sorption isotherm measurements were performed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 49 publications
5
26
2
Order By: Relevance
“…After a few weeks, crystallization and phase separation occurred in all p-peel-based films plasticized with sorbitol. Sorbitol crystallization was also found in other biopolymer films, like maize starch- 27 potato protein isolate (PPI)-, 12 and potato starch-based films 11 For p-peel-based films, Kang and Min also reported wet and sticky films, when plasticized with more than 33% w/w glycerol and stored at 23 C and 52% RH. In contrast to these findings, p-peel-based films in this study, containing glycerol concentrations of 50% to 70%, were neither sticky nor wet when stored at 23 C and 50% RH.…”
Section: Statistical Analysis and Experimental Designmentioning
confidence: 88%
See 4 more Smart Citations
“…After a few weeks, crystallization and phase separation occurred in all p-peel-based films plasticized with sorbitol. Sorbitol crystallization was also found in other biopolymer films, like maize starch- 27 potato protein isolate (PPI)-, 12 and potato starch-based films 11 For p-peel-based films, Kang and Min also reported wet and sticky films, when plasticized with more than 33% w/w glycerol and stored at 23 C and 52% RH. In contrast to these findings, p-peel-based films in this study, containing glycerol concentrations of 50% to 70%, were neither sticky nor wet when stored at 23 C and 50% RH.…”
Section: Statistical Analysis and Experimental Designmentioning
confidence: 88%
“…30,31 The absence of increase or decrease of EMC with increasing plasticizer concentration could be explained by inability to incorporate/release further water molecules into/from the polymer matrix. 12 However, moisture contents of p-peel-based films plasticized with glycerol are much higher than those plasticized with sorbitol, confirming the higher ability of glycerol to attract and retain water. Comparing equivalent plasticizer contents, Schäfer et al found similar results for PPI-based films and Shaw et al for WPI-based films.…”
Section: Equilibrium Moisture Contentmentioning
confidence: 94%
See 3 more Smart Citations